2011
DOI: 10.1007/s00381-011-1661-0
|View full text |Cite
|
Sign up to set email alerts
|

The importance of very early decompressive craniectomy as a prevention to avoid the sudden increase of intracranial pressure in children with severe traumatic brain swelling (retrospective case series)

Abstract: Considering the anamnestic data, it could be useful to perform DC at 20-22 mmHg ICP in young patients in order to prevent the potential of very fast brain swelling if there is no possibility to perform durotomy within 20 min after the onset of raising the ICP. It is especially considerable in poor countries where the emergency route could be less organized because of locations of building and extreme load of the staff. Further controlled trials are necessary to evaluate the indication and standardization of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…A number of studies have documented the role of DC in TBI in adults, but very few studies can be found in relation to paediatric age group [3,5,6,[11][12][13][14][15]. Similarly, reports both for [3,8,13] and against DC [6,28,29] can be found in the literature.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A number of studies have documented the role of DC in TBI in adults, but very few studies can be found in relation to paediatric age group [3,5,6,[11][12][13][14][15]. Similarly, reports both for [3,8,13] and against DC [6,28,29] can be found in the literature.…”
Section: Discussionmentioning
confidence: 88%
“…Different types of DC have been described in the literature, which includes bifrontal, bitemporal, wide unilateral and bilateral hemicraniectomies with/without duraplasty, among others [3,13,15]. Diffuse cerebral oedema (DCE) is one specific entity which occurs much more commonly in children and can lead to a profound rise in intracranial hypertension if not treated early.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, some studies suggest early DC may improve outcomes in pediatric severe TBI [10-12]. Several surgical techniques have been used in previous studies, such as unilateral DC and bifrontal DC.…”
Section: Discussion/conclusionmentioning
confidence: 99%